PROSPECTS OF IMPLEMENTATION OF MECHANISMS IN RURAL AREAS IN MANAGEMENT OF HOUSING CONSTRUCTION (British Journal of Global Ecology and Sustainable Development, 2023)
This article presents the results of a survey conducted on the example of the city of Tashkent in order to study the role of managing service companies in housing and communal services, as well as achievements.